2007
DOI: 10.1063/1.2720751
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and ferroelectric properties of highly dense lead-free piezoelectric (K0.5Na0.5)NbO3 thick films by aerosol deposition

Abstract: Lead-free piezoelectric thick films of (K0.5Na0.5)NbO3 were fabricated by aerosol-deposition method. The thickness of KNN film was 7.1μm and fully dense films were obtained. The dielectric constants ε3T∕ε0 of the as-deposited and annealed films at 1kHz were 116 and 545, respectively, which are higher than any previously reported values for lead-free piezoelectric thin/thick films, either without or with heat treatment. The ferroelectric properties were improved after annealing and the maximum values of Pr=8.1μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 14 publications
3
107
0
Order By: Relevance
“…Table 2 summarizes the permittivity of NKN films prepared by various processes, indicating rather small values of 37 by RF magnetron sputtering 28) and 545 by aerosol deposition. 29) High permittivity values above 500 have been reported for epitaxial and (001)-oriented 0.5NKN films, 10,11) whereas the non-oriented 0.5NKN film in the present study showed a relatively high value. To date various compositions of NKN films have been prepared, but only the composition of 0.5NKN film has been focused on in the literature.…”
Section: )mentioning
confidence: 56%
“…Table 2 summarizes the permittivity of NKN films prepared by various processes, indicating rather small values of 37 by RF magnetron sputtering 28) and 545 by aerosol deposition. 29) High permittivity values above 500 have been reported for epitaxial and (001)-oriented 0.5NKN films, 10,11) whereas the non-oriented 0.5NKN film in the present study showed a relatively high value. To date various compositions of NKN films have been prepared, but only the composition of 0.5NKN film has been focused on in the literature.…”
Section: )mentioning
confidence: 56%
“…More detailed conditions of the ADM and LLO processes are delineated in our previous reports. 11,[54][55][56] Both Raman spectra before and after the LLO clearly manifest the tetragonal/orthorhombic symmetries of L-KNN maintained during the LLO process, 58 and high crystallinity was confirmed by X-ray diffraction (XRD) patterns (Figs. S2(a) and S2(b)).…”
mentioning
confidence: 90%
“…[45][46][47][48][49][50][51][52] Nevertheless, the deposition or post-crystallization of KNN-based materials involves difficult processing due to the loss of vaporizable alkaline compositions and slow deposition rates. 53,54 Recently, our group developed a new deposition method, aerosol deposition method (ADM), which is a gas-deposition process that uses as-synthesized particles directly with an accelerated gas to build colloidal aerosol flows. [54][55][56] Herein, we demonstrate a high-performance KNN-based flexible piezoelectric energy harvester (f-PEH) using the ADM with the laser lift-off (LLO) process and investigate overall biocompatibility features ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] The deposition mechanism of AD process is ascribed to room temperature impact solidification from the impact of fine ceramic particles accelerated by the carrier gas. 1,3 During the coating process, submicron powders in aerosol state are accelerated with carrier gas flow, and collide directly on the substrate with high velocity over hundreds m/s.…”
Section: Introductionmentioning
confidence: 99%